PENGARUH KINERJA KEUANGAN PADA HARGA SAHAM (STUDI PADA PERUSAHAAN LQ 45) - Siana, Anggita Inggit; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test and to analyze the influence of financial performance on stock price. The financial performance variable is proxy with the Current Ratio, Return on Asset, Debt to Equity, and Price Earnings Ratio, meanwhile the stock price is the proxy from the investor variable. The sample collection has been done by using purposive sampling method in which the sample selection of the company is collected by using the criteria and certain consideration from the researcher. Based on the sample selection method, 10 companies which are included in LQ45 consecutively for 5 years from 2009 to 2013 have been selected as samples. The quantitative analysis method is used as the research method in which the data analysis method is based on the data which can be calculated in order to generate the quantitative assessment. Meanwhile, the multiple linear regressions are used as the analysis technique. The results of this research show i.e.: (a) Current Ratio has positive influence to the stock price; (b) Return on Asset has positive influence to the stock price; (c) Debt to Equity Ratio does not have any influence to the stock price; and (d) Price Earnings Ratio does not have any influence to the stock price.Keywords: Current Ratio, Return On Asset, Debt to Equity, Price Earnings Ratio, and Stock Price